Perancangan Sistem Informasi Akuntansi Pokok Pada CV. Kekha Mustika - Adinda Maharani; Ira Novianty (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
CV. Kekha Mustika is a manufacturing company located in Cimahi City, the company's activities are producing kitchen sets. Recording is done is still simple and has not applied the applicable accounting principles. The background of the owners and employees is one of the obstacles so that the company has not improved the recording system which has shortcomings. This study is intended to design a basic accounting information system in the company. This study uses a qualitative descriptive method and has four stages of the process. The first stage is system analysis, the author analyzes the system that applies in the company, the second stage is making a proposal for the design of the basic accounting system based on the company's needs, the third stage is testing, and the last stage is the implementation of the system design that has been made. This research shows that CV. Kekha Mustika does not yet have a proper system, so there is no financial information that can be used by stakeholders. The results of this study are the proposed design of the basic accounting information system which includes proposed systems/procedures, document designs, financial reports, and examples of implementation applied to the company.